THE EFFECT OF RENTABILITY, PROFITABILITY, AND SOLVABILITY TO AUDIT DELAY - Riani Riani; Riyanto Wujarso Riyanto Wujarso (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2021)
This study aims to analyze the effect of rentability, profitability, and solvability on audit delay. The population in this study was 5 manufacturing companies listed on the Stock Exchange in 2015-2018. Sampling using purposive sampling. The sample in this study were 20 manufacturing companies (food and beverage subsector) listed on the Indonesia Stock Exchange (IDX). Data analysis techniques using multiple linear regression analysis. The results of this study indicate that partially rentability and profitability had a strength significant effect on audit delay, and solvability has a weak significant effect on audit delay. Simultaneously rentability, profitability, and solvability together have a significant influence on audit delay. Adjusted R-square value is 0,516, meaning that the magnitude of the coefficient of determination is 0.516 which states that the independent variable explains the dependent variable of 51.6 %. The remaining 48.4 % is influenced by other variables that is not in researched.